Ketamine Use in Hysterosalpingography (the Jimah Procedure): A Follow-Up of Bilateral Tubal Evaluation of 27 Infertile Women at a Teaching Hospital, Ghana - Bashiru Babatunde Jimah; Anthony Baffour Appiah; Benjamin Dabo Sarkodie; Dorothea Anim (Radiology Research and Practice)
Background. Pain, anxiety, and distress are common in radiological investigations including hysterosalpingogram (HSG). Studies suggest that sedation allows patients to better tolerate diagnostic imaging and image-guided procedures by relieving anxiety, discomfort, and pain. This study aimed at assessing the safety and effectiveness of ketamine use in HSG and the proportion of true positive bilateral tubal blockage during HSG using the Jimah Procedure. Methods. We performed repeated HSG workup under IV ketamine (20–40 mg/mL) sedation for 27 infertile women at the Cape Coast Teaching Hospital. The exclusion criteria included unilateral tubular blockage, acute infection of the vagina or cervix, active vaginal bleeding, glaucoma, and high blood pressure at the time of the study. Data were entered with Microsoft Excel and analyzed using SPSS version 21. Results. A total of 27 patients (age range: 25–48 years) previously diagnosed of bilateral tubal blockage or spasm were enrolled for the repeat HSG procedure. The median age was 34 years (IQR: 32–37), while secondary infertility (20) (74.1%) was the commonest indication. None of the patients reported of pain or distress during or after the procedure. Two (7.4%) women vomited after HSG. Twelve patients (44.4%) had bilateral tubal blockage (true positive), while tubal patency was seen in 15 (55.6%) patients on HSG under ketamine sedation. Conclusion. This study found IV ketamine sedation produces profound anesthesia and analgesia and eliminates tubal spasm. We recommend that radiologists in developing countries should consider sedating patients during HSG and documenting observations and patients’ feedback to help assess safety and effectiveness in local settings.